First-Principles Calculation and Analysis of the Magnetic and Mechanical Properties of Mo2C with Vacancy Defects and Substitutional Doping - Xiaoliang Qing; Jing Guo; Xiaoxiao Liu; Qian Zhang; Tammam Kaid; Nathan Outterside; Cong Tang; Li Wang; Qingxiang Yang; Xuejun Ren (Crystals)
In this study, the first-principles method is adapted to establish key data for β-Mo2C with various point defects. A particular focus is comparatively studying the effects of point vacancies and different substitutional doping elements on the structures and electronic, magnetic and mechanical properties of β-Mo2C. The calculation results show that vacancy defects and substitutional doping have different impacts on the magnetism and bulk modulus of Mo2C. Data for the effect of different substitutional doping elements (V, Cr, Co, Fe, Ni and W) on the physical and mechanical properties/behaviours are established and analysed. The changes in key magnetic properties (local and total magnetic moments) associated with different point substitutional doping elements are comparatively analysed with reference to the data of Mulliken atomic charge, bond population, density of states (DOS) and band structures. The correlation between doping elements and changes in magnetic moment and bulk modulus is discussed. The influence of doping elements on the magnetic moment of 3D Mo2C is also compared to their effects on a two-dimensional Mo2C monolayer. The potential applications of DFT modeling and data for future research and development related to materials and processing are discussed.